Patient Perspectives on Removing Adult Tonsillectomy and Septoplasty from the Government Health Insurance Plan in a Publicly Funded Health Care System. (April 2021) - Grose, Elysia; Chiodo, Sarah; Levin, Marc; Eskander, Antoine; Lin, Vincent; Hubbard, Brad; Chiodo, Albino
In several publicly funded health care systems, including Ontario, Canada, adult tonsillectomies and septoplasties have been suggested to be removed or "delisted" from the government health insurance plan. Thus, the objective of this study was to explore patient perspectives regarding out of pocket (OOP) payment for these procedures. An anonymous survey was administered to patients consented to undergo a tonsillectomy or septoplasty at a community otolaryngology—head and neck surgery (OHNS) practice. The survey asked patients if they would pay the projected cost for their surgery OOP and the maximum amount of time they would wait for their surgery. The survey also contained questions on socioeconomic status and disease severity. Seventy-one patients were included. Overall, 21% of patients were willing to pay OOP for their surgery. Forty-nine percent of patients reported that the maximum amount of time they would be willing to wait for their surgery was 2 to 6 months. There was no significant correlation found between any of the demographic variables or disease severity and willingness to pay OOP for these surgeries. In this study, a small percentage of patients who met the clinical indications for a tonsillectomy or a septoplasty would pay for their surgery in the event that it was not covered by the government health insurance plan. These surgeries are common operations and delisting them could potentially decrease the provision of these services and have a significant impact on Canadian OHNS practices.